Putative Role of Prostaglandin Receptor in Intracerebral Hemorrhage - Mohan, Shekher; Ahmad, Abdullah S.; Glushakov, Alexander; Chambers, Chase; Dore, Sylvain (Frontiers in Neurology, 2012)
Each year, approximately 795,000 people experience a new or recurrent stroke. Of all strokes, 84% are ischemic, 13% are intracerebral hemorrhage (ICH) strokes and 3% are subarachnoid hemorrhage (SAH) strokes. Despite the decreased incidence of ischemic stroke, there has been no change in the incidence of hemorrhagic stroke in the last decade. ICH is a devastating disease 37-38% of patients between the ages of 45-64 die within 30 days. In an effort to prevent ischemic and hemorrhagic strokes we and others have been studying the role of prostaglandins and their receptors. Prostaglandins are bioactive lipids derived from the metabolism of arachidonic acid. They sustain homeostatic functions and mediate pathogenic mechanisms, including the inflammatory response. Most prostaglandins are produced from specific enzymes and act upon cells via distinct G-protein coupled receptors. The presence of multiple prostaglandin receptor’s cross-reactivity and coupling to different signal transduction pathways allow differentiated cells to respond to prostaglandins in a unique manner. Due to the number of prostaglandin receptors, prostaglandin-dependent signaling can function either to promote neuronal survival or injury following acute excitotoxicity, hypoxia, and stress induced by ICH. To better understand the mechanisms of neuronal survival and neurotoxicity mediated by prostaglandin receptors, it is essential to understand downstream signaling. Several groups including ours have discovered unique roles for prostaglandin receptors in rodent models of ischemic stroke, excitotoxicity, and Alzheimer disease, highlighting the emerging role of prostaglandin receptor signaling in hemorrhagic stroke with a focus on cyclic-adenosine monophosphate (cAMP) and calcium (Ca2+) signaling. We review current ICH data and discuss future directions notably on prostaglandin receptors, which may lead to the development of unique therapeutic targets against hemorrhagic stroke and brain injuries alike.